2020
DOI: 10.31314/jsig.v3i2.659
|View full text |Cite
|
Sign up to set email alerts
|

INTEGRASI OPEN DATA, URUN DAYA, DAN PEMETAAN PARTISIPATIF DALAM PENGELOLAAN SUMBER DAYA ALAM DAN LINGKUNGAN HIDUP (Integration of Open Data, Crowdsourcing, and Participatory Mapping for Natural Resources and Environmental Management)

Abstract: Data and information availability area main obstacles in the natural resources and environmental (SDAL) management in developing countries. Technology development in society should be able to support SDAL management to be more efficient and effective while empowering the local human resources through open data, crowdsourcing, and participatory mapping. This article aims to explain the integration scheme of open data, crowdsourcing, and participatory mapping in SDAL management. The integration can be initiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Many studies have revealed how public policies affect the flood management system, but communication barriers are vital because they can have an impact on the coordination, integration, and synergy of all parties (Dede et al, 2020). Currently, there is no review-based study available regarding the communication of flood management policies in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed how public policies affect the flood management system, but communication barriers are vital because they can have an impact on the coordination, integration, and synergy of all parties (Dede et al, 2020). Currently, there is no review-based study available regarding the communication of flood management policies in Indonesia.…”
Section: Introductionmentioning
confidence: 99%